Pendampingan Sekolah Peduli Tuberkulosis Paru Berbasis Lingkungan Sehat - Kusmiyati, Kusmiyati; Sinaga, Enni Rosida; Selasa, Pius; Waangsir, Ferry William Frangky (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Environmental conditions can influence the occurrence of environmental-based diseases. Pulmonary tuberculosis (TB) is an environmental-based disease that is still a problem in Indonesia. The aim: to increase knowledge about pulmonary TB and increase sanitation facilities to improve indoor air circulation. This community service was carried out by a team of lecturers and students from the Kupang Ministry of Health Health Polytechnic Sanity Study Program. The activity partners were students of SMPK Adisucipto Penfui Kupang. Activities began with situation analysis, activity planning, implementation of counseling, mentoring as well as monitoring and evaluating activities. Community service activities in the form of assistance to schools caring for pulmonary TB at SMPK Adisucipto Penfui. This activity consists of counseling about preventing pulmonary TB disease and providing facilities to improve air circulation in classrooms. The results of the evaluation of student knowledge using a questionnaire showed that there was an increase in student knowledge. Providing facilities in the form of fans increases the availability of facilities to improve room air circulation so that the room air is more comfortable and feels cooler. Counseling with lectures and giving leaflets increases knowledge about pulmonary TB. The increase in the number of sanitation facilities has increased indoor air circulation making it more comfortable. Follow-up: Continuous assistance with broader targets (UKS, teachers, parents).